Role of surface oxide layers in the hydrogen embrittlement of austenitic stainless steels: A TOF-SIMS study. (November 2019) - Izawa, Chika; Wagner, Stefan; Deutges, Martin; Martín, Mauro; Weber, Sebastian; Pargeter, Richard; Michler, Thorsten; Uchida, Haru-Hisa; Gemma, Ryota; Pundt, Astrid
Abstract: Hydrogen environment embrittlement (HEE) of low-nickel austenitic stainless steels (AISI 300 series) with different chemical compositions was studied focusing on the impact of the steels surface oxides, grain sizes and dislocation arrangements. The susceptibility of the steels to HEE is judged with respect to the relative reduction of area (RRA), where the HEE susceptibility is lower for larger RRA values. For many AISI 300 steels a linear trend is observed correlating RRA and the probability of strain induced martensite formation in tensile tests. Some steels, however, depart from the general trend, revealing greater HEE resistances. A careful examination of possible factors influencing HEE of the investigated steels reveals that high RRA values are linked to a specific type of oxide layer, namely the "high constant level oxide", as categorized by TOF-SIMS evaluation. Thus, this type of oxide layer may be able to lower the steels HEE susceptibility. Other types of surface oxides, grain sizes and dislocation arrangements in the matrix of the particular AISI 300 steels appear to be of secondary importance. Graphical abstract: Image 1